Evaluation of UIN North Sumatra E-Learning Program During the Covid-19 Period - Usiono Usiono; Salim Salim; Zunidar Zunidar; Ahmad Taufik Al Afkari Siahaan (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
Pandemic Covid-19 requires online learning (E-Learning) at every tertiary institution, including UIN North Sumatra (UIN-SU) Medan. The readiness of institutions and campus academicians in facilitating students is not a major problem for UIN-SU Medan, because pre-co-leaders 19 leaders issued a learning system policy of 70% face-to-face and 30% e-learning. This paper aims to evaluate the UIN-SU Medan e-learning program during the COVID 19. This evaluation effort was carried out using a Context, Input, Process, Product (CIPP) study. This research criterion is a standard of compatibility between expectations and reality. Through interviews, observations, documentation, and dissemination of data obtained questionnaires, for further analysis using reduction techniques, data presentations, and concluding. The findings of this research indicate that the UIN-SU Medan e-learning program is well implemented, although it does not display significant changes, this can be seen from (1) context: e-learning learning provides easy access to student learning and is accompanied by policies that follow government regulations and survive the development of technology; (2) input: Online learning system; (3) process: pre-covid19 70% face-to-face 30% e-learning, covid19 period 100% e-learning; (4) product: lectures continue to run smoothly, and students can attend lectures from various places. Even so, there are obstacles in the form of internet network disruption, limitations on student quotas, and system downtime that require maintenance efforts.